The Effect Of Human Resource Development On People And Organizational Culture On Employee Performance At Wyndham Opi Hotel Palembang - Iraawan, Rikky; Naruliza, Esty; Mario, Asma (Jurnal Fokus Manajemen, 2025)
This study aims to prove whether there is an effect of job descriptions and worker This study aims to determine the effect of job descriptions and job specifications on employee performance at PT Cipta Prima Synergy in Palembang City. This study uses a quantitative approach with multiple linear regression analysis methods. The sample in this study amounted to 60 employees selected through probability sampling technique. The results of the analysis show that the research instrument has met the validity requirements because the calculated r value is greater than the r table (0.3), and is reliable with a Cronbach's Alpha value of 0.07 which is close to 1. Partial test (t test) shows that both job descriptions and job specifications have a significant influence on employee performance. Likewise with the results of the simultaneous test (F test), which shows that the two variables together have a significant effect on employee performance. The object of this research is PT Cipta Prima Synergy, a national private company incorporated in the field of coal transportation services as well as the sale of spare parts for heavy equipment vehicles, located on Jl. Pangeran Ayin No. 302/06-07 RT.03/RW.05, Sukamaju Village, Sako District, Palembang City.